2022
DOI: 10.3390/ijerph191911901
|View full text |Cite
|
Sign up to set email alerts
|

Towards Meaning in Life: A Path Analysis Exploring the Mediation of Career Adaptability in the Associations of Self-Esteem with Presence of Meaning and Search for Meaning

Abstract: In the contemporary world of work, workers are engaged more frequently in career choices to cope with changing work and working conditions. In this scenario, the well-being of workers is under threat. This study aims to examine the effect of career adaptability as a preventive resource on the relationship between self-esteem and meaning in life. Three-hundred Italian workers (67.3% females, mean age = 41.90; SD = 12.54) completed an online survey enclosing the Career Adapt-Abilities Scale, the Rosenberg self-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…The findings of this study contribute to the career construction theory (Savickas, 2005(Savickas, , 2020, as career adaptability works as a personal source of cognition through which individuals cope with challenges. It can be developed over time as the findings of this study claim that leadership humility, through inspirational and encouraging behaviors, increases this psychological source which enhances optimization, meaning, satisfaction, development, and success about careers (Chui, Li, & Ngo, 2022;Gori et al, 2022;Li et al, 2015). Our findings are also in line with the findings of some recent and earlier studies (Gong et al, 2023;Zeng et al, 2022) by explaining the intervening mechanism of career adaptability, as leadership humility as an organizational and environmental source increases the cognition and motivation level of individuals which enforce them for the demonstration of willingness to face the uncertainty and complexity in the careers due to which they become able to attain the career success.…”
Section: Discussionmentioning
confidence: 93%
“…The findings of this study contribute to the career construction theory (Savickas, 2005(Savickas, , 2020, as career adaptability works as a personal source of cognition through which individuals cope with challenges. It can be developed over time as the findings of this study claim that leadership humility, through inspirational and encouraging behaviors, increases this psychological source which enhances optimization, meaning, satisfaction, development, and success about careers (Chui, Li, & Ngo, 2022;Gori et al, 2022;Li et al, 2015). Our findings are also in line with the findings of some recent and earlier studies (Gong et al, 2023;Zeng et al, 2022) by explaining the intervening mechanism of career adaptability, as leadership humility as an organizational and environmental source increases the cognition and motivation level of individuals which enforce them for the demonstration of willingness to face the uncertainty and complexity in the careers due to which they become able to attain the career success.…”
Section: Discussionmentioning
confidence: 93%
“…The Life Design paradigm offers the theoretical framework for career construction to encompass the complex dynamics and multiple nonlinear interactions involved in the evolution of people's life and career trajectories (Reid, 2016;Savickas, 2011;Savickas et al, 2009). Savickas (2005) defining career paths in the third millennium as unpredictable, identified career adaptability as the core psychological resource to enable individuals to respond adaptively to continuous career changes (Gori et al, 2022). In Savickas' theories, successful career construction is a continuous process of active adaptation resulting from person-environment integration, where people must actively build their careers, responding effectively to environmental challenges through acquiring career resources (Savickas, 2002(Savickas, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that career adaptation was associated with adaptive variables such as cognitive ability, big five traits, self-esteem, etc., adaptive responses such as career exploration, and self-efficacy, and adaptive outcomes such as job/career/school satisfaction, job stress, employability, etc. [ 35 ] A study of nursing students before internship found that perceived stress before internship was negatively associated with pre-internship career adaptation, the correlation coefficient was − 0.69 [ 36 ].…”
Section: Introductionmentioning
confidence: 99%